Carbetocin compared to oxytocin in emergency cesarean section: a randomized trial. (March 2016) - Razali, Nuguelis; Md Latar, Ida Lilywaty; Chan, Yoo Kuen; Omar, Siti Zawiah; Tan, Peng Chiong
Abstract: Objective: To evaluate the uterotonic effect of carbetocin compared with oxytocin in emergency cesarean delivery. Study design: Participants were randomized to intravenous bolus injection of 100 mcg carbetocin or 10 IU oxytocin after cesarean delivery of the baby. The primary outcome is any additional uterotonic which may be administered by the blinded provider for perceived inadequate uterine tone with or without hemorrhage in the first 24 hours after delivery. Secondary outcomes include operating time, perioperative blood loss, change in hemoglobin and hematocrit levels, blood transfusion and reoperation for postpartum hemorrhage. Results: Additional uterotonic rates were 107/276 (38.8%) vs. 155/271 (57.2%) [RR 0.68 95% CI 0.57–0.81 p  < 0.001; NNTb 6 95% CI 3.8–9.8], mean operating time 45.9 ± 16.0 vs. 44.5 ± 13.1 minutes p  = 0.26, mean blood loss 458 ± 258 vs. 446 ± 281 ml p  = 0.6, severe postpartum hemorrhage (≥1000 ml) rates 15/276 (5.4%) vs. 10/271 (3.7%) p  = 0.33 and blood transfusion rates 6/276 (2.2%) vs. 10/271 (3.7%); p  = 0.30 for carbetocin and oxytocin arms respectively. There was only one case of re-operation (oxytocin arm). In the cases that needed additional uterotonic 98% (257/262) was started intraoperatively and in 89% (234/262) the only additional uterotonic administered was an oxytocin infusion over 6 hours. Conclusion: Fewer women in the carbetocin arm needed additional uterotonics but perioperative blood loss, severe postpartum hemorrhage, blood transfusion and operating time were not different.